Upaya Guru Dalam Meningkatkan Kemampuam Baca Al-Qur’an Siswa Melalui Program Matrikulasi di SD IT Madani 2 Kota Payakumbuh - Finda Fadilla; M. Isnando Tamrin; Alimir A; Diyan Permata Yanda (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This research aims to find out how teachers make efforts to improve students’ Al-Qur’an reading skills through the matriculation program at SD IT Madani 2 Payakumbuh City. This study used qualitative research methods. The informants in this research were teachers at SD IT Madani 2, Payakumbuh City as key informants and supporting informants, namely students at SD IT Madani 2, Payakumbuh City. The data collection techniques used are observation, interviews and documentation. The data analysis used by the Milles and Uberman models is data reduction, data presentation and drawing conclusions. The data validity technique uses data triangulation. Based on the results of research conducted at SD IT Madani 2, Payakumbuh City, it can be concluded that efforts have been made by teachers to improve students’ Al-Qur’an reading skills through the matriculation program at SD IT Madani 2, Payakumbuh City. There have been efforts made, including teachers teaching the Qur’an. These include teachers teaching the Qur’an, first emphasizing the correct pronunciation of the letters called makhrijul letters, teachers teaching recitation material up to the level of reading proficiency, teachers teaching students to read the Qur'an according to the rules of science. tajwid, guiding students to be fluent in reading the Al-Qur’an, motivating students to be enthusiastic in reading the Al-Qur’an and also providing rewards to students who are able to read the Al-Qur’an well and correctly according to the rules of science recitation.